Exploration of Neusilin® US2 as an Acceptable Filler in HPMC Matrix Systems-Comparison of Pharmacopoeial and Dynamic Biorelevant Dissolution Study - Tomáš Bílik; Jakub Vysloužil; Martina Naiserová; Jan Muselík; Miroslava Pavelková; Josef Mašek; Drahomíra Čopová; Martin Čulen; Kateřina Kubová (MDPI AG, 2022)
Modern pharmaceutical technology still seeks new excipients and investigates the further use in already known ones. An example is magnesium aluminometasilicate Neusilin® US2 (NEU), a commonly used inert filler with unique properties that are usable in various pharmaceutical fields of interest. We aimed to explore its application in hypromellose matrix systems (HPMC content 10-30%) compared to the traditionally used microcrystalline cellulose (MCC) PH 102. The properties of powder mixtures and directly compressed tablets containing individual fillers NEU or MCC, or their blend with ratios of 1.5:1, 1:1, and 0.5:1 were investigated. Besides the routine pharmaceutical testing, we have enriched the matrices' evaluation with a biorelevant dynamic dissolution study and advanced statistical analysis. Under the USP apparatus 2 dissolution test, NEU, individually, did not provide advantages compared to MCC. The primary limitations were the burst effect increase followed by faster drug release at the 10-20% HPMC concentrations. However, the biorelevant dynamic dissolution study did not confirm these findings and showed similarities in dissolution profiles. It indicates the limitations of pharmacopoeial methods in matrix tablet development. Surprisingly, the NEU/MCC blend matrices at the same HPMC concentration showed technologically advantageous properties. Besides improved flowability, tablet hardness, and a positive impact on the in vitro drug dissolution profile toward zero-order kinetics, the USP 2 dissolution data of the samples N75M50 and N50M50 showed a similarity to those obtained from the dynamic biorelevant apparatus with multi-compartment structure. This finding demonstrates the more predictable in vivo behaviour of the developed matrix systems in human organisms.